2007
DOI: 10.1029/2006jd007865
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and visible radiation at Barrow, Alaska: Climatology and influencing factors on the basis of version 2 National Science Foundation network data

Abstract: [1] Spectral ultraviolet (UV) and visible irradiance has been measured near Barrow, Alaska (71°N, 157°W), between 1991 and 2005 with a SUV-100 spectroradiometer. The instrument is part of the U.S. National Science Foundation's UV Monitoring Network. Here we present results based on the recently produced ''version 2'' data release, which supersedes published ''version 0'' data. Cosine error and wavelength-shift corrections applied to the new version increased biologically effective UV dose rates by 0-10%. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 57 publications
5
85
0
Order By: Relevance
“…Similarly, the summer periods of 2008 and 2009, in which marked volcanic particle extinction effects were observed due to the Kasatochi and Sarychev eruptions are marked by two narrow grey vertical bands labelled with letters K and S, respectively. measurements recorded at Barrow, Bernhard et al (2007) found a very good correlation between the AOD FWNIP and AOD(500 nm) values, defined for an overall regression coefficient R ¼ þ0.91. To verify the reliability of the present estimates of AOD FWNIP and evaluate their consistency with the AOD(500 nm) evaluations derived from the SP02 sun-photometer measurements, Fig.…”
Section: Time Series Of Aod At Barrow (Alaska)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the summer periods of 2008 and 2009, in which marked volcanic particle extinction effects were observed due to the Kasatochi and Sarychev eruptions are marked by two narrow grey vertical bands labelled with letters K and S, respectively. measurements recorded at Barrow, Bernhard et al (2007) found a very good correlation between the AOD FWNIP and AOD(500 nm) values, defined for an overall regression coefficient R ¼ þ0.91. To verify the reliability of the present estimates of AOD FWNIP and evaluate their consistency with the AOD(500 nm) evaluations derived from the SP02 sun-photometer measurements, Fig.…”
Section: Time Series Of Aod At Barrow (Alaska)mentioning
confidence: 99%
“…Comparing the measurements of AOD FWNIP with those of AOD(500 nm) directly obtained from the Cimel sun-photometer April 1977 to August 2010, while exponent a was evaluated using the algorithm of Bernhard et al (2007). The two FWNIP series of AOD and a are compared with (1) those of AOD(500 nm) derived from the SP02 Carter Scott sun-photometer measurements (solid squares), (2) those of a determined from the overall set of SP02 (solid squares) and SP022 sun-photometer (open squares) measurements, as performed by the NOAA/GMD group during the 9-year period from February 2002 to October 2010; and (3) those determined from the Level 2.0 AERONET sun-photometer measurements performed at Barrow over the 12-year period from June 1999 to September 2010 (grey diamonds).…”
Section: Time Series Of Aod At Barrow (Alaska)mentioning
confidence: 99%
“…The Brewer network provides a variety of products such as the total columns of ozone (TOC) (Kerr et al, 1981), SO 2 (Cappellani and Bielli, 1995) and NO 2 (Cede et al, 2006;Diémoz et al, 2014), the aerosol optical depth (AOD) Gröbner and Meleti, 2004;Meleti and Cappellani, 2000) as well as global and direct irradiance spectra (Bais et al, 1993(Bais et al, , 1996. These measurements have supported scientific research for more than 30 years, enabling the investigation of their shortand long-term variability (Glandorf et al, 2005;Weatherhead et al, 1998;Zerefos, 2002) and interactions among them and among other atmospheric constituents (Bernhard et al, 2007). Additionally, good-quality ground-based measurements are very useful for the validation of satellite products which, under specific conditions, may be highly uncertain (Fioletov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Solar radiation with wavelengths shorter than 290 nm is entirely blocked by the atmosphere, while for longer wavelengths the fraction that penetrates to the surface depends mainly on the solar zenith angle, the composition of the atmosphere and the characteristics of the surface (Kerr and Fioletov, 2008). The interaction between the UV radiation, the atmospheric constituents and the characteristics of the surface is complicated and not yet fully understood (Bernhard et al, 2007;Kerr and Fioletov, 2008;Meinander et al, 2009). The geophysical parameters that mainly affect the levels of the surface UV irradiance are: ozone, clouds, surface reflectivity and aerosols (Arola et al, 2003;Bais et al, 1993;Bernhard et al, 2007;WMO, 2007).…”
Section: Introductionmentioning
confidence: 99%